Produção acadêmica, rede científica e formação da comunidade epistêmica no Programa de Pós-Graduação em Geografia da Universidade Federal de Uberlândia: uma contribuição dos estudos métricos da informação - Souza, Kelma Patrícia de (2023)
The research carried out the application of techniques of metric information studies, to evaluate academic production, constituted in the dissertations and theses defended in the Graduate Program in Geography of the Federal University of Uberlândia between 2000 and 2020. The objective was to identify, through the scientific network constituted in this context, the formation of the epistemic community from the citations referenced in the mentioned productions. To this end, an exploratory documentary research was carried out on the assumptions of a quantitative approach, going through the strategies of profile analysis, guided by bibliometrics and scientometrics, as well as the calculation of production and citation indicators. The sources of data collection were documentary, electronic pages, defense minutes, academic curriculum, dissertations and theses. Therefore, the information from these documents was recorded in spreadsheets; while for its visualization, the Gephi software was used. We addressed the constitution of the scientific network, with 44 teachers who guided the work, in addition to presenting results and discussion around the connections made by these, training institutions and the program itself. This relationship began in 1997, the year the creation of the master's degree course were approved — the doctorate began to be offered in 2003. Dissertations and theses were located and described through production indicators. The profile of the students was also drawn regarding sex, nationality and academic background; academic production by level and year; lines of research; profile of the advisors; themes; and, in view of these, notes for the construction of a thesaurus for the geographical area. Within the time frame studied, 505 masters and 206 PhDs in Geography were graduated. Then, a study was carried out from the origins of academic training to the professional profile of these graduates. From the citation indicators, 72,226 references indicated in productions were found, such as books (most of the total raised) and other information communication channels, occasions in which the Portuguese language predominated. In order to obtain scientific consistency, authors were also extracted physical person(s) in a synchronous manner from 5 types of documents: book, book chapter, article published in a journal, dissertation and thesis. In this methodology, 49,289 references and 59,296 authors from a universe of 23,693 specific authors were filtered, with Milton Santos, Roberto Lobato Corrêa and Beatriz Ribeiro Soares, among the most cited. Finally, the epistemic communities were presented, built by 26 advisors, who guided 10 or more studies. In addition, 289 authors mentioned in these productions were considered, present in the 10 largest quantities of citations, distributed inthought networks in urban, rural, environmental and geographic education themes. From this, it was found that the scientific community of PPGeo/UFU has a heterogeneous characteristic, due to the breadth of authorship, low centralization of ideas within the same group and fractionation of the scientific network into networks of thought. Thus, a diagnosis of the program was drawn up, aiming to contribute to consultations and guide actions for its expansion. Finally, a course evaluation methodology was presented, guided by metric information studies.